The Environmental Scenario Generator (ESG): a distributed environmental data archive analysis tool - E A Kihn; M Zhizhin; R Siquig; R Redmon (Data Science Journal, 2006)
The Environmental Scenario Generator (ESG) is a network distributed software system designed to allow a user to interact with archives of environmental data for the purpose of scenario extraction, data analysis and integration with existing models that require environmental input. The ESG uses fuzzy-logic based search tools to allow a user to look for specific environmental scenarios in vast archives by specifying the search in human linguistic terms. For example, the user can specify a scenario such as a "cloud free week" or "high winds and low pressure" and then search relevant archives available across the network to get a list of matching events. The ESG hooks to existing archives of data by providing a simple communication framework and an efficient data model for exchanging data. Once data has been delivered by the distributed archives in the ESG data model, it can easily be accessed by the visualization, integration and analysis components to meet specific user requests. The ESG implementation provides a framework which can be taken as a pattern applicable to other distributed archive systems.